Early prediction of therapy outcome in patients with high-risk soft tissue sarcoma using positron emission tomography - Kasper, Bernd; Dietrich, Sascha; Dimitrakopoulou-Strauss, Antonia; Strauss, Ludwig G.; Haberkorn, Uwe; Ho, Anthony Dick; Egerer, Gerlinde (Onkologie, 2008)
Background: We used 2-deoxy-2-[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) to evaluate the FDG uptake in patients with soft tissue sarcoma (STS). Treatment effect was assessed with regard to prediction of therapy outcome. Patients and Methods: The ongoing evaluation includes 27 patients with high-risk STS receiving chemotherapy consisting of doxorubicin and ifosfamide (AI-G regimen), or etoposide, ifosfamide and doxorubicin (EIA regimen). Patients were examined using PET prior to onset of therapy, and after completion of the first cycle of AI-G and after 2 cycles of EIA chemotherapy, respectively. Restaging according to RECIST was performed after 6 cycles of AI-G or 4 cycles of EIA chemotherapy and served as reference. Results: Clinical outcome of 27 evaluable patients was as follows: 2 patients with no evidence of disease, 7 with partial remission, 14 with stable disease, and 4 patients with progressive disease. A significant difference of the progression-free survival for patients with a decrease in the standardised uptake value (SUV; responders) in comparison to patients with an increase or stable SUV (non-responders) could be demonstrated (p = 0.0187). Conclusion: On the basis of these data, prediction of chemo-sensitivity of the tumour and moreover of the therapy outcome might be possible.
Gesehen am 13.10.2021